Association between sugar-sweetened beverages and duration of physical exercise with psychological symptoms among Tibetan university students at high altitude - Song, Wei; Su, Fan; Li, Shengpeng; Song, Yongjing; Chai, Guangxin (Frontiers in Psychology, 2024)
Background Sugar-sweetened beverages(SSBs) and duration of physical exercise are strongly associated with physical health. Unfortunately, there are few studies focused on the association with psychological symptoms, let alone Tibetan university students at high altitudes in China. Methods A stratified cluster sampling method was used to include 8,268 Tibetan university students aged 19-22 years in Qinghai and Tibet, both of which are high-altitude regions of China.Self-assessment questionnaires on SSBs, duration of physical exercise, and psychological symptoms were administered. The chi-square test and logistic regression analysis were used to analyze the associations among them.The detection rate of psychological symptoms among Tibetan university students in high-altitude areas of China was 16.7%, with in girls (18.2%) higher than that in boys (14.8%), and the difference was statistically significant (χ 2 = 11.73, P < 0.01). The proportion of SSBs for university students ≤1 time/week, 2-5 times/week, and ≥6 times/week were 54.2%, 24.3%, and 21.5%, respectively. The proportion of duration of physical exercise for >60 min/d was only 5.4%.Logistic regression analysis showed that compared with the SSBs ≤1 time/week group of university students, SSBs 2-5 times/week (OR = 1.45, 95% CI: 1.24-1.70) and ≥6 times/week (OR = 3.06, 95% CI: 2.62-3.57) had an increased risk of psychological symptoms (P < 0.001). In the reference group, the risk of psychological symptoms was also significantly increased in the group of university students with duration of physical exercise >60 min/d (OR = 2.08, 95% CI:1.48-2.93), and the risk of psychological symptoms was also significantly increased in the group 字体: (默认)Times New Roman,